2021
DOI: 10.1016/j.psj.2020.11.062
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary energy levels on performance and carcass yield of 2 meat-type broiler lines housed in hot and cool ambient temperatures

Abstract: Two meat-type broiler lines, line A and line B were fed experimental diets from 22–42 d with objectives to determine the effects of dietary metabolizable energy ( ME ) levels on feed intake ( FI ), performance, body composition, and processing yield as affected by environmental grow-out temperatures. Two thousand fifty male chicks from line A and 2,050 male chicks from line B were reared in 90-floor pens, 45 chicks per pen utilizing primary breeder nutrition and hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
(23 reference statements)
1
6
0
Order By: Relevance
“…Improvement in BW and FCR by increasing dietary amino acid density has been documented (Maharjan et al, 2020(Maharjan et al, , 2021Vieira & Angel, 2012). In the current study by decreasing dietary energy level the density of amnio acids (Lysine and total sulphur amino acids) increased per unit of energy which had a possitive effect on chicken's final performance.…”
Section: Growth Performance and Carsass Traitsmentioning
confidence: 48%
See 2 more Smart Citations
“…Improvement in BW and FCR by increasing dietary amino acid density has been documented (Maharjan et al, 2020(Maharjan et al, , 2021Vieira & Angel, 2012). In the current study by decreasing dietary energy level the density of amnio acids (Lysine and total sulphur amino acids) increased per unit of energy which had a possitive effect on chicken's final performance.…”
Section: Growth Performance and Carsass Traitsmentioning
confidence: 48%
“…Aftab (2019) reported that the modern broiler chickens need less ME than that recommended by breeder companies. Different studies have proven that the proper ratio of dietary energy to protein/amino acid is very vital for optimal performance of broilers (Maharjan et al, 2020, 2021). Improvement in BW and FCR by increasing dietary amino acid density has been documented (Maharjan et al, 2020, 2021; Vieira & Angel, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of the varying conditions was intentionally not assessed to avoid misleading inferences based on insufficient statistical power. However, all effect sizes came from factors tested within the same genetic line; therefore, the generalizations in our study do not include relationships among genetic lines [ 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of each study uses a temperature that does not exceed the temperature that has been mentioned so that the energy content of metabolism is neither too high nor too low. According to Maharjan et al (2021), dietary energy levels affect energy retention efficiency. The metabolic energy requirement of the finisher ration is 2800-3200 kcal/kg.…”
Section: Ration Consumptionmentioning
confidence: 99%